INVENTION OF EPHIFIT ORCHIDS IN WAISAI, WAIGEO DISTRICT IN RAJA AMPAT REGION - Mambrasar, Yasper Michael; Respatijarti, Respatijarti; Kendarini, Niken (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2016)
Waigeo island is known as the biggest island in Raja Ampat Regency, West Papua. Therefore, types of flora and fauna at this island are similar with the flora and fauna in Papua island although there are some endemics of Waigeo island. Papua is known of the diversity of orchid especially epiphyte, but diversity related to character, habitat, spread area and living pattern of the orchid in natural location is still unknown. This research aimed at obtaining information of germ plasma of epiphyte orchid comprising of types and amount as well as the host tree from orchid at forest area throughout the stream Swainbon river. This research is performed at Swainbon river included in Waisai village, district of South Waigeo, Raja Ampat regency started on Oktober 2008 â Desember 2008. The research using line transect method. Result of this research obtained 18 genera and 37 species in 1852 individuals. Species with the most population in the location is Cadetia taylori. The tree as the host tree traider comprise 27 types and the most of type utilized as the host tree is Intsia sp.Keywords : Epiphyte Orchid, Waisai, South Waigeo distric, Raja Ampat Regency